2008
DOI: 10.1051/gse:2008029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of strong selection for the PrP major gene on genetic variability of four French sheep breeds(Open Access publication)

Abstract: -Effective selection on the PrP gene has been implemented since October 2001 in all French sheep breeds. After four years, the ARR ''resistant'' allele frequency increased by about 35% in young males. The aim of this study was to evaluate the impact of this strong selection on genetic variability. It is focussed on four French sheep breeds and based on the comparison of two groups of 94 animals within each breed: the first group of animals was born before the selection began, and the second, 3-4 years later. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Using these methods, r GBV is greatest when Ne and genome size are small and the reference population size is big. Published studies on genetic diversity in sheep (Huby et al, 2003;Palhiere et al, 2008;Garcia-Gamez et al, 2012) and goat (Araújo et al, 2006;Ribeiro et al, 2012) breeds have shown that small ruminant populations are heterogeneous and display high effective population sizes compared with most selected cattle breeds. This is positive for the long term selection response but, with the methods used here, negatively affects the genomic prediction accuracies.…”
Section: The Selection Modelmentioning
confidence: 99%
“…Using these methods, r GBV is greatest when Ne and genome size are small and the reference population size is big. Published studies on genetic diversity in sheep (Huby et al, 2003;Palhiere et al, 2008;Garcia-Gamez et al, 2012) and goat (Araújo et al, 2006;Ribeiro et al, 2012) breeds have shown that small ruminant populations are heterogeneous and display high effective population sizes compared with most selected cattle breeds. This is positive for the long term selection response but, with the methods used here, negatively affects the genomic prediction accuracies.…”
Section: The Selection Modelmentioning
confidence: 99%
“…With the recent development of molecular technologies, genomic selection is now used for several species, and major genes can be identified and sequenced. Selection for specific alleles of several major genes is already implemented, such as the prion protein ( PrP ) gene for scrapie resistance in dairy sheep and goats [ 1 , 2 ]. The genomic best linear unbiased prediction (GBLUP) approach is based on the assumption that many quantitative trait loci (QTL), each with a small effect, contribute to genetic variation [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason why several studies proposed different selection regimes in European sheep breeds evaluating their consequences on breed genetic variability. Usually studies are performed using pedigree information, molecular markers data or a combination of both (Álvarez et al, 2007, 2009; Palhiere et al, 2008; Windig et al, 2004, 2007).…”
Section: Discussionmentioning
confidence: 99%